Glucocorticoids and cortical decoding in the phobic brain. (30th June 2020) - Schwab, Simon; Federspiel, Andrea; Morishima, Yosuke; Nakataki, Masahito; Strik, Werner; Wiest, Roland; Heinrichs, Markus; de Quervain, Dominique; Soravia, Leila M.
Highlights: Patients with spider phobia demonstrate higher neural decoding of spider images in the left and right anterior insula and the anterior cingulate cortex (ACC). Decoding in these areas are correlated with experienced fear. Cortisol treatment involves reduced fear and decoding in the precuneus, the cerebellum and the opercular cortex. Placebo administration is associated with higher fear and decoding in the insula, the AAC and the right frontal pole. Abstract: Glucocorticoids reduce phobic fear in anxiety disorders and enhance psychotherapy, possibly by reducing the retrieval of fear memories and enhancing the consolidation of new corrective memories. Glucocorticoid signaling in the basolateral amygdala can influence connected fear and memory-related cortical regions, but this is not fully understood. Previous studies investigated specific pathways moderated by glucocorticoids, for example, visual-temporal pathways; however, these analyses were limited to a-priori selected regions. Here, we performed whole-brain pattern analysis to localize phobic stimulus decoding related to the fear-reducing effect of glucocorticoids. We reanalyzed functional magnetic resonance imaging (fMRI) data from a previously published study with spider-phobic patients and healthy controls. The patients received glucocorticoids or a placebo before the exposure to spider images. There was moderate evidence that patients with phobia had higher decoding of phobic content in the anterior cingulate cortex (ACC) and the left and right anterior insula compared to controls. Decoding in the ACC and the right insula showed strong evidence for correlation with experienced fear. Patients with cortisol reported a reduction of fear by 10–13%; however, there was only weak evidence for changes in neural decoding compared to placebo which was found in the precuneus, the opercular cortex, and the left cerebellum.